2015
DOI: 10.1080/09712119.2015.1031775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protected organic acid blends on growth performance, nutrient digestibility and faecal micro flora in growing pigs

Abstract: This study was conducted to evaluate the effects of dietary supplementation of protected organic acid blends on growth performance, nutrient digestibility and faecal micro flora in growing pigs. A total of 100 crossed [(Landrace × Yorkshire) × Duroc] with an initial body weight (BW) of 23.4 ± 1.27 kg were used in a six-week trial. Pigs were randomly allocated into one of four treatments (five replications with five pigs per pen) in a randomly complete block design based on their BW. Treatments consisted of CON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 20 publications
6
45
1
Order By: Relevance
“…These results are in agreement with our previous studies showing that dietary supplementation of POA can improved the growth performance of growing and finishing pigs (Upadhaya et al, 2014;Upadhaya et al, 2016). Consistent with our findings, some researchers have shown positive effects with single or blends of dietary acidifiers.…”
Section: Growth Performancesupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in agreement with our previous studies showing that dietary supplementation of POA can improved the growth performance of growing and finishing pigs (Upadhaya et al, 2014;Upadhaya et al, 2016). Consistent with our findings, some researchers have shown positive effects with single or blends of dietary acidifiers.…”
Section: Growth Performancesupporting
confidence: 94%
“…The OA can improve their growth performance and reduce the post-weanling diarrhea (Kiarie et al, 2008;Wang et al, 2009). In our previous studies, we have noted that medium chain fatty acids (MCFA) combined with OA can be considered as an alternative of additive to improve the performance growing pigs (Upadhaya et al, 2016), finishing pigs (Upadhaya et al, 2014) and sows (Devi et al, 2016).…”
mentioning
confidence: 99%
“…Active ingredients such as citric acid, malic acid, fumaric acid, and MCFAs are dispersed in a matrix of shell material, a lipid which can allow the active components to reach the intestine in an intact form, and be released slowly by the reaction of lipase from the intestine thereby showing beneficial effects to animals [10,28]. It has been previously reported that using the same product of protected blend of OA and MCFA supplementation in diets improved growth performance of piglets, and growing and finishing pigs [7,10,29] as well as laying hens [20]. In this study, we also observed that the BWG and FCR were linearly improved when broilers were fed the diets supplemented with the blend of OAs and MCFAs.…”
Section: Growth Performancementioning
confidence: 99%
“…The increase of Lactobacillus population has positive effects on intestinal function by reducing the survival rate of enteric pathogens due to the low pH resulting from the acid produced by the fermentation of Lactobacillus. As the microbial pathogenic population becomes reduced, the metabolic requirements of the microbes is reduced and the availability of dietary energy and nutrients to the host animal is increased, leading to enhanced growth rate and feed efficiency [10].…”
Section: Excreta Microbialmentioning
confidence: 99%
See 1 more Smart Citation